State of Exchange : Migrant NGOs and the Chinese Government - Hsu, Jennifer Y. J (Book collections on Project MUSE., 2017)
"China's rapid socio-economic transformation has generated extraordinary movements of people from rural areas to urban centres. At the peak of labour migration in the early 2000s, some 100 to 200 million people moved to cities in search of higher wages and better standards of living. State of Exchange examines how--despite the authoritarian nature of the Chinese state--non-governmental organizations in China have increased dramatically as central and local states tacitly allow migrant NGOs to deliver community services to workers in Beijing and Shanghai. Interacting with spaces and layers of the state at various levels of government, NGOs conduct and scale up their programs, while the state, in turn, engages with NGOs as a means to remain relevant and further legitimize its own interests. Jennifer Hsu uses a new conceptual framework to assess state-NGO relations and ultimately to reveal how NGOs navigate the complex web of central and local government bodies to lend stability to, and form mutually beneficial relationships with, the Chinese state. As North Africa and the Middle East move into a new era of politics, the Chinese experience outlined in this book will serve as a blueprint for better understanding the best practices and lessons learned for state-society relationships at the central and local levels."--